1971
DOI: 10.1016/0005-2736(71)90096-4
|View full text |Cite
|
Sign up to set email alerts
|

Ox peripheral nerve myelin membrane. Purification and partial characterization of two basic proteins

Abstract: SUMMARYTwo basic proteins were purified from the peripheral nervous system. The isolation was achieved by (I) delipidation with chloroform-butanol mixtures, dry acetone, and dry ether, (2) acid extraction at pH 2 and then (3) dialysis against distilled water, lyophilization, and solubilization in pH-Io.7 buffer. Further purification steps included: (4) ion exchange chromatography on QAE-Sephadex G-25 and (5) gel filtration on Sephadex G-75. Each of the two basic proteins was shown to be homogeneous by disc ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…No stimulation of lymphocytes from the above rabbits was observed when they were cultured with any of the following antigens: basic proteins of bovine central (26) and peripheral (27) nerve tissue, human aqueous muscle extract, and hen egg white lysozyme (a nonrelated protein). The stimulation indices obtained with the mitogens phytohemagglutinin and concanavalin A were about 30.…”
Section: Resultsmentioning
confidence: 96%
“…No stimulation of lymphocytes from the above rabbits was observed when they were cultured with any of the following antigens: basic proteins of bovine central (26) and peripheral (27) nerve tissue, human aqueous muscle extract, and hen egg white lysozyme (a nonrelated protein). The stimulation indices obtained with the mitogens phytohemagglutinin and concanavalin A were about 30.…”
Section: Resultsmentioning
confidence: 96%
“…In experimental allergic encephalomyelitis (EAE), the central nervous system (CNS) cohnterpart of EAN, the encephalitogen is the myelip basic protein. PNS myelin has two basic proteins, P1 and P2 [ l l , 13,191, and the latter (called P,L by London [35] and BF by Uyemura et al [66]) has been suggested to be the neuritogen [l, 2, 11, 291. Brostoff et al [12] have reported that a neuritogenic determinant is present within a peptide representing the NH,-terminal 2 1 amino acids of P2 [12].…”
mentioning
confidence: 99%
“…It was denoted P2 or P2L by London [72] and by Abramsky and London [1,2] or P~ by Brostoff and Eylar [23]. Two basic proteins were found in myelin of bovine, rabbit, guinea pig, and human peripheral nerves.…”
Section: Experimental Models and Guillain-barr6 Syndromementioning
confidence: 99%